STRATEGI PENGEMBANGAN USAHA KECIL MENENGAH (UKM) KEMPLANG PANGGANG DI KECAMATAN MARTAPURA KABUPATEN OGAN KOMERING ULU TIMUR - Indriani (Sekolah Tinggi Ilmu Pertanian (STIPER) Belitang, 2018)
Strategy for the Development of Small and Medium Enterprises (UKM) kemplanganggang in Martapura District, Ogan Komering Ulu Timur Regency. The method used in this study used a saturated sample method, the samples taken were SMEs, kemplang traders and the Department of Industry and Trade in the city of Martapura. The types of data used in this study include primary and secondary data, which are analyzed using the SWOT matrix. The results of the research in the field obtained an average of 2.93 internal factors and 3.26 external factors, this means that the Kemplanganggang UKM in Martapura District, East OKU Regency is in position II with a concentration strategy through Horizontal integration, from the SWOT analysis it can be concluded that UKM Baked kemplang has weaknesses and threats that must be minimized so that it can develop more advanced in the future, there are several ways that have been analyzed, namely by increasing kemplang production, making packaging more attractive and using labels, promoting through social media, increasing forms. kemplang variants to make it more attractive, and add outlets and expand the network by entering areas where there is no kemplang production.